Use of Sodium Bicarbonate in Cardiac Arrest: Current Guidelines and Literature Review - Velissaris, Dimitrios (J Clin Med Res, 2016)
The aim of the review was to summarize the literature over the last 25 years regarding bicarbonate administration in out-of-hospital cardiac arrest. A PubMed search was conducted using the terms “bicarbonates” and “cardiac arrest”, limited to human studies and reviews published in English (or at least with a meaningful abstract in English) in the last 25 years. Clinical and experimental data raised questions regarding the safety and effectiveness of sodium bicarbonate (SB) administration during cardiac arrest. Earlier advanced cardiac life support (ACLS) guidelines recommended routine bicarbonate administration as part of the ACLS algorithm, but recent guidelines no longer recommend its use. The debate in the literature is ongoing, but at the present time, SB administration is only recommended for cardiac arrest related to hypokalemia or overdose of tricyclic antidepressants. Several studies challenge the assumption that bicarbonate administration is beneficial for treatment of acidosis in cardiac arrest. At the present time, there is a trend against using bicarbonates in cardiac arrest, and this trend is supported by guidelines published by professional societies and organizations.